Exploring the role of visual perceptual grouping on the audiovisual integration of motion. - Sanabria, D; Soto-Faraco, S; Spence, C (2004)
In the present study, we explored the role of visual perceptual grouping on audiovisual motion integration, using an adaptation of the crossmodal dynamic capture task developed by Soto-Faraco et al. The principles of perceptual grouping were used to vary the perceived direction (horizontal vs vertical) and extent of apparent motion within the visual modality. When the critical visual stimuli, giving rise to horizontal local motion, were embedded within a larger array of lights, giving rise to the perception of global motion vertically, the influence of visual motion information on the perception of auditory apparent motion (moving horizontally) was reduced significantly. These results highlight the need to consider intramodal perceptual grouping when investigating crossmodal perceptual grouping.